Update of the risk assessment on 3‐monochloropropane diol and its fatty acid esters. (10th January 2018) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hoogenboom, Laurentius (Ron); et al.
Abstract: The CONTAM Panel updated the assessment of the risks for human health related to the presence of 3‐monochloropropane diol (3‐MCPD) and its fatty acid esters in food published in 2016 in view of the scientific divergence identified in the establishment of the tolerable daily intake (TDI) in the Joint FAO/WHO Expert Committee on Food Additives and Contaminants (FAO/WHO) report published in 2017. In this update, dose–response analysis was performed following the recent EFSA Scientific Committee guidance on the use of benchmark dose (BMD) approach in risk assessment, and a review of available data on developmental and reproduction toxicity was included. The outcome of this review indicates that in rats short‐term exposure to 3‐MCPD above 1 mg/kg body weight (bw) per day can induce reduced sperm motility associated with reduced male fecundity. Decreased sperm count and histopathological changes in the testis and epididymis were observed following longer treatment periods at higher doses. Regarding increased incidence kidney tubular hyperplasia, BMD analysis using model averaging resulted in a BMDL10 of 0.20 mg/kg bw per day in male rats, which was selected as the new Reference Point (RP) for renal effects. For the effects on male fertility, decreased sperm motility was selected as the most sensitive relevant endpoint and a BMDL05 of 0.44 mg/kg bw per day was calculated. The RP for renal effects was considered to derive an updated group TDI of 2 μg/kg bw per day for 3‐MCPD and its fatty acid esters and was considered protective also for effects on male fertility. The established TDI of 2 μg/kg bw per day is not exceeded in the adult population. A slight exceedance of the TDI was observed in the high consumers of the younger age groups and in particular for the scenarios on infants receiving formula only. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2016.4426/full